2010
DOI: 10.1021/np9004129
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones from Anthemis melanolepis and Their Antibacterial and Cytotoxic Activities. Prediction of Their Pharmacokinetic Profile

Abstract: Nine sesquiterpene lactones, anthemin A (1), 1alpha-hydroxydeacetylirinol-4alpha,5beta-epoxide (2), anthemin C (3), tatridin A (4), 1-epi-tatridin B (5), anthemin B (6), 6-deacetyl-beta-cyclopyrethrosin (7), elegalactone A (8), and 1beta,4alpha,6alpha-trihydroxyeudesm-11-en-8alpha-12-olide (9), were isolated from the aerial parts of A. melanolepis in addition to eight known flavonoids and three phenolic acids. Compounds 1, 3, and 6 are new natural products. The structures of the compounds were deduced by spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 30 publications
0
13
0
4
Order By: Relevance
“…The organic phase was concentrated under vacuum to dryness and yielded a lipophilic residue (0.14%). [9]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The organic phase was concentrated under vacuum to dryness and yielded a lipophilic residue (0.14%). [9]…”
Section: Methodsmentioning
confidence: 99%
“…[7] It is also used for the treatment of cough and cold. [8] The genus Anthemis is characterized mainly by the presence of sesquiterpene lactones, belonging to germacranolides, eudesmanolides, guaianolides[9,10] and flavonoids. [11] The literature survey on A. wiedemanniana revealed the presence of sesquiterpene lactones of germacrane, eudesmane and guaianolide type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…桉烷倍半萜类化合物多样化的生物活性尤为引人 关注, 例如: 抗艾滋病病毒 [1] , 抑制晶状体醛糖还原酶 (AR, Aldose Reductase)( 糖性白内障相关酶) [2] , 抗肿 瘤 [3~4] , 抗菌 [5] , 抗炎 [6] , 抗疟疾, 细胞生长抑制, 植物 生长调节和降血糖 [7] 等活性 [8] , 广泛的生物活性使这类 化合物成为化学家追求的合成目标靶分子. 我们发现从植物中间锦鸡儿中分离得到的天然产 物桉烷-4(15)-烯-1β,7α-二醇(Y019)在 12 μg/mL 水平具 有抗稻瘟酶活性 [9] , 是潜在的抗肿瘤, 抗真菌的先导化 合物.…”
unclassified
“…They constitute a valuable chemotaxonomic material and might be also decisive for the medicinal value of the raw material, as in Chamomillae anthodium, Cnici benedicti herba, Arnicae anthodium, Millefolii herba, Chrysanthemi partheni herba, Cichorii radix et herba. A recent study has revealed antibacterial and cytotoxic activities of sesquiterpene lactones [1]. These compounds can be detected through visual chromatography and isolated by simple column chromatography, with silica gel as the adsorbent.…”
mentioning
confidence: 99%